2018
DOI: 10.1002/cctc.201701949
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Graphene‐Supported Iron Catalyst for Highly Chemoselective Hydrogenation of Nitroarenes

Abstract: An itrogen-doped graphene-supported iron catalyst was used for the first time in the hydrogenation of aseries of nitroarenes to give the corresponding amines with excellent activity and chemoselectivity under mild reactionc onditions. Physicochemical characterization of the catalyst by transmission electron microscopy,X -ray diffraction, X-ray photoelectrons pectroscopy,a nd Mçssbauers pectroscopy revealed the formation of iron particles with an iron oxide core and am etallic iron shell that were coated by af … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…[44] It showed that excellent performance and improvement could be achieved by using graphene materials as catalyst supports in various reactions. [45] However, the preparation process of GO is demanding.…”
Section: The Structural Of Traditional Supported Metal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] It showed that excellent performance and improvement could be achieved by using graphene materials as catalyst supports in various reactions. [45] However, the preparation process of GO is demanding.…”
Section: The Structural Of Traditional Supported Metal Catalystsmentioning
confidence: 99%
“…According to recent research, GO not only has a larger specific surface area than CNTs, but also uses the surface area more efficiently because of the special two‐dimensional planar microstructure [44] . It showed that excellent performance and improvement could be achieved by using graphene materials as catalyst supports in various reactions [45] . However, the preparation process of GO is demanding.…”
Section: The Develop Of Metal‐2d Semiconductor Hybrid Nano‐structure ...mentioning
confidence: 99%
“…[4] One of the well-established methodology of reduction of nitroarenes was described by Béchamp with more than a stoichimoetric amount of iron powder in acidic conditions. [5] More efficient and chemoselective iron-catalyzed methodologies involving hydrosilylation, [6] hydrogenation, [7] hydrogen transfer [8] or other reductants [9] were also recently reported. Cascade reactions involving iron-catalyzed reduction of nitroarenes were also reported.…”
mentioning
confidence: 99%